PENGARUH MODEL PEMBELAJARAN BEHAVIORISTIK DAN REWARD TERHADAP KEDISIPLINAN BELAJAR SISWA KELAS V UPT SDN 020 BUKIT PAYUNG - Siti Hanifah; Nasrul; Kasman Ediputra; Astuti; Fadhilaturrahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the influence of the Behavioristic Learning Model and Rewards on students’ learning discipline in elementary school. The research was conducted at UPT SDN 020 Bukit Payung with a total of 36 fifth-grade student participants. This study employed a quasi-experimental method using a Nonequivalent Control Group Design with a quantitative approach. The instruments used to measure students’ learning discipline included a questionnaire, teacher observation sheet, and student observation sheet, while the pretest and posttest for mathematics and Rewards were in the form of essay and multiple-choice questions. Quantitative data were analyzed using SPSS version 20. The results showed that the learning discipline of students who received the Behavioristic Learning Model combined with Rewards was higher than that of students who learned through the conventional model. Based on the Independent Samples t-test, the significance value obtained was 0.000 < 0.05, with the average posttest score of the experimental class being 78.17 and the control class 76.67. This indicates that the behavioristic model and Rewards are more effective in improving students’ learning discipline. Therefore, this model can be used as an alternative strategy in mathematics learning to enhance learning discipline among elementary school students.